Up and out of poverty - Xi Jinping (Foreign Languages Press Co. Ltd, 2016)
As the first personal monograph of General Secretary Xi Jinping, this book faithfully records his practices of carrying out the party's line, policies and regulations, building well-off society in an all-around way and promoting the cause of socialism with Chinese characteristics; shows his key thoughts in economic, political, cultural, social, ecological civilization construction and Party building; reflects his firm political stand, value pursuit and thinking style, thus of great theoretical value and practical value.